Pengaruh Promosi Terhadap Minat Kunjungan Wisatawan Pada Objek Sumur Putri di Kecamatan Teluk Betung Utara Kota Bandar Lampung - Muhamad Aldo Efrenza; Muhamad Syamsul Maarif (Business and Enterpreneurship Journal (BEJ), 2023)
The purpose of this study was to determine the effect of promotion on tourist interest in the Sum Putri tourism object in TelukBetung Utara sub-district, Bandar Lampung city. The data used in this study were primary data. Furthermore, the data collection technique used in this study was a survey that used Use Google Forms to collect data. In this study the researchers used the t test and coefficient test methods with the help of the smart plss program version 2. Based on the results of the research, the R² value lies at 0 R² 1, an R² value close to 1, which means the model is getting better. Meanwhile, the value of R² which is zero means that there is no relationship between the dependent variable and the explanatory variable. From the table, with the location of R² 1 with a value of 0 0.999 1, this means that the variance of the Effect of Promoting the Variance of Economic Growth is 99. 9%, while the remaining 0.01% is explained by other variables outside the model. Keywords :Promotion, and Visiting Interest